2019
DOI: 10.1002/jhet.3538
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and In Vitro Anticancer Activities of Diethylene Glycol Tethered Isatin‐1,2,3‐triazole‐coumarin Hybrids

Abstract: A series of novel diethylene glycol tethered isatin‐1,2,3‐triazole‐coumarin hybrids 9a–l were designed, synthesized, and evaluated for their in vitro anticancer activities against HepG2 (liver carcinoma), Hela (cervical cancer), A549 (lung adenocarcinoma), DU145 (prostatic cancer), SKOV3 (ovarian carcinoma), MCF‐7 (breast cancer), and drug‐resistant MCF‐7/DOX (doxorubicin‐resistant MCF‐7) human cancer cell lines. The results showed that most of the synthesized hybrids exhibited considerable in vitro activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Firstly, the scavenging activity of the compounds was evaluated on ABTS (2,2 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt), DPPH (2,2-diphenyl-1-picrylhydrazyl) and galvinoxyl radicals as Trolox (a Vitamin E analogue) equivalent antioxidant capability (TEAC). The results showed that, whereas 1 did not exhibit radical scavenging activity, 2 resulted more active than Trolox against the ABTS•+ radical (EC 50 30.83 µM) and 3 displayed better antioxidant activity than Trolox against ABTS•+, DPPH and galvinoxyl radicals (EC 50 values of 39.98, 150.99 and 13.19 µM, respectively). It is likely that such differences in antioxidant activity may rely on the differences in the relative positions of hydroxy groups [31].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, the scavenging activity of the compounds was evaluated on ABTS (2,2 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt), DPPH (2,2-diphenyl-1-picrylhydrazyl) and galvinoxyl radicals as Trolox (a Vitamin E analogue) equivalent antioxidant capability (TEAC). The results showed that, whereas 1 did not exhibit radical scavenging activity, 2 resulted more active than Trolox against the ABTS•+ radical (EC 50 30.83 µM) and 3 displayed better antioxidant activity than Trolox against ABTS•+, DPPH and galvinoxyl radicals (EC 50 values of 39.98, 150.99 and 13.19 µM, respectively). It is likely that such differences in antioxidant activity may rely on the differences in the relative positions of hydroxy groups [31].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…When PC3 and DU145 human PCa cells were treated with different concentrations of both 4-MMPB and 18 for 24, 48 and 72 h, a dose-dependent and time-dependent decrease in the survival of the cells was exhibited. PC3 cells resulted to be more sensitive than DU145 cells to both inhibitors (IC 50 Concerning the mechanism of action, it was found that 5-farnesyloxycoumarin acts as a cytotoxic agent causing chromatin condensation and DNA damage and induces the arrest of the cell cycle in G 0 /G 1 phase. A similar study was carried out on 8-farnesyloxycoumarin (19, Figure 8) by Hosseinymehr and collaborators [46].…”
Section: Anticancer Activitymentioning
confidence: 99%
See 3 more Smart Citations